Preparation of monodisperse SiO2 nanorods with hollow structure and parameters affecting the length-diameter ratio. Issue 8 (14th June 2021) - Yang, Qi Qi; Chen, Xiao Li; He, Ying; Lai, Jia Qi; Xiong, Yi; Shen, Qian; Zhou, Xing Chao; Shao, Bin; Ma, Yi Long; Guo, Dong Lin; Li, Ke Jian; Li, Chun Hong; et al.
Abstract: Monodisperse SiO2 nanorods with hollow structure were prepared using FeOOH as a template. Powder X-ray diffraction, scanning electron microscopy, transmission electron microscopy, and nitrogen adsorption-desorption isotherms were utilized to characterize the products. With a FeCl3 concentration of 0.1 M, the average length and width of the prepared hollow SiO2 nanorods were 397 nm and 116 nm, respectively, and the average length-diameter ratio was calculated as 3.4. The average size of the nanopores of the amorphous SiO2 shell were measured as 2.5 nm. Furthermore, increasing the concentration of Cl − ions improved length-diameter ratios of the FeOOH nanorod template and hollow SiO2 nanorods. Graphical Abstract: